ANALISIS PENGARUH WAKTU TAHAN SALT BATH NITRIDING TERHADAP KETEBALAN NITRIDE LAYER DAN KEKERASAN PERMUKAAN PADA MATERIAL SUH35 (JIS: SUH35) - Ni'am Sofi; Fatimah Dian Ekawati; Budi Santoso (Jurnal Ilmiah Teknik Mesin, 2019)
Time is a parameter that is very influential on the productivity and product quality from the nitriding process. This study aims to find out how much effect of the holding time in salt bath nitriding process to the nitride layer thickness and surface hardness of SUH35 material. This salt bath nitriding process used chemical salt with cyanide content (CNˉ) 1.5% - 4.5%, and cyanate content (CNOˉ) 28% - 32%. The workpiece used in this study is a cylindrical SUH35 material with diameter 5 mm. Temperature that used for salt bath nitriding process is 580 ° C with a variation of the holding time is 20 minutes, 25 minutes and 35 minutes. From this study, results of the data obtained are, with a holding time 20 minutes the average thickness of the nitride layer SUH35 material is 12.74 µm and the average surface hardness is 556.96 Hv. With a holding time 25 minutes the average thickness of the nitride layer SUH35 material is 16.07 µm and the average surface hardness is 792.18 Hv. With a holding time 35 minutes the average thickness of the nitride layer SUH35 material is 20.17 µm and the average surface hardness is 989.94 Hv.